Unresolved mystery of cyclic nucleotide second messengers, periplasmic acid phosphatases and bacterial natural competence - Kristina Kronborg; Yong Everett Zhang (Microbial Cell)
We recently characterized the competitive inhibition of cyclic AMP (cAMP) on three periplasmic acid phosphatases, AphAHi, NadNHi, and eP4 (HelHi), in Haemophilus influenzae Rd KW20. This inhibitory effect is vital for orchestrating the nutritional growth and competence development in KW20. Initially discovered in Escherichia coli, the function of AphA remains however obscure. This study investigates the regulation of E. coli aphA expression under nutrient starvation conditions. Using transcriptional reporters with truncated aphA promoter sequences, we found that starvations of carbon and phosphate, but not amino acid, stimulated aphA expression through distinct promoter regions. Deletions of crp or cyaA abolished aphA expression, confirming their crucial roles. Conversely, CytR deletion increased aphA expression, suggesting CytR's role as a repressor of aphA expression. Additionally, we extended the study of three other second messengers, i.e., cyclic GMP, cyclic UMP, and cyclic CMP, each sharing structural similarities with cAMP. Notably, cGMP competitively inhibits AphAHi's acid phosphatase activity akin to cAMP. In contrast, both cUMP and cCMP stimulate AphAHi's phosphatase activity in a concentration dependent manner. Collectively, these data imply a complicated connection between nucleotide metabolism, AphA, cyclic purine and pyrimidine nucleotides in bacterial nutrient uptake and natural competence.